2010
DOI: 10.1016/j.jcrs.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro lens capsule model for investigation of posterior capsule opacification

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…14,19 -23 With respect to testing IOLs using such systems, the body of literature is limited. 14,19,22,24 Liu et al 14 initially demonstrated that an IOL could impede growth to some degree using the human capsular bag system developed in Norwich. In the present study, we made a modification in the protocol such that the capsular bag containing the IOL was inverted, resulting in the anterior capsule being closest to the plastic dish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,19 -23 With respect to testing IOLs using such systems, the body of literature is limited. 14,19,22,24 Liu et al 14 initially demonstrated that an IOL could impede growth to some degree using the human capsular bag system developed in Norwich. In the present study, we made a modification in the protocol such that the capsular bag containing the IOL was inverted, resulting in the anterior capsule being closest to the plastic dish.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that pinning directly through the capsule can distort the capsular bag and, therefore, prevent the IOL locating in its natural position; however, using pins to secure the capsular bag has provided results that reflect clinical features of PCO, thus demonstrating the value of this approach. Another variant of the capsular bag system that was recently published by Cleary et al 19 retains the ciliary body, which is pinned to a silicon ring. Using this method, the capsular bag is effectively suspended and can house an IOL, which can also be observed.…”
Section: Discussionmentioning
confidence: 99%
“…The development of capsular bag models allowed for the introduction of an IOL (Cleary et al, 2010;Dawes et al, 2012;De Groot et al, 2005;Duncan et al, 1997;Eldred et al, 2014;Liu et al, 1996) and thus provide an alternative experimental system for IOL development and importantly permit IOLs to be tested in a human system. For example, the capsular bag model served as an invaluable tool in the development of the Bag-in-the-lens IOL developed by Prof. Tassignon (De Groot et al, 2005), which is now commercially available.…”
Section: Capsular Bagsmentioning
confidence: 99%
“…Efforts were also being made to establish a suspended capsular bag system, such that ElOsta et al (2003) initially secured the periphery of the capsular bag to a lens holder using medical grade glue and this permitted IOLs to be introduced. An advance on this method was developed by Cleary et al (2010), which retained the ciliary body and zonular fibres in association with the capsular bag. The ciliary body is pinned to a silicon ring.…”
Section: Capsular Bagsmentioning
confidence: 99%
“…The model previously described by Liu et al 13 and developed by Cleary et al 14 was employed. Pairs of donor eyes (corneas previously removed for eye banking; Table) were obtained within 48-hours post mortem with national research ethics committee approval and used in accordance with the tenets of the Declaration of Helsinki.…”
Section: Capsular Bag Preparationmentioning
confidence: 99%